A retrospective analysis of benefits and impacts of U.S. renewable portfolio standards. (September 2016) - Barbose, Galen; Wiser, Ryan; Heeter, Jenny; Mai, Trieu; Bird, Lori; Bolinger, Mark; Carpenter, Alberta; Heath, Garvin; Keyser, David; Macknick, Jordan; Mills, Andrew; Millstein, Dev
Abstract: As states consider revising or developing renewable portfolio standards (RPS), they are evaluating policy costs, benefits, and other impacts. We present the first U. S. national-level assessment of state RPS program benefits and impacts, focusing on new renewable electricity resources used to meet RPS compliance obligations in 2013. In our central-case scenario, reductions in life-cycle greenhouse gas emissions from displaced fossil fuel-generated electricity resulted in $2.2 billion of global benefits. Health and environmental benefits from reductions in criteria air pollutants (sulfur dioxide, nitrogen oxides, and particulate matter 2.5) were even greater, estimated at $5.2 billion in the central case. Further benefits accrued in the form of reductions in water withdrawals and consumption for power generation. Finally, although best considered resource transfers rather than net societal benefits, new renewable electricity generation used for RPS compliance in 2013 also supported nearly 200, 000 U. S.-based gross jobs and reduced wholesale electricity prices and natural gas prices, saving consumers a combined $1.3–$4.9 billion. In total, the estimated benefits and impacts well-exceed previous estimates of RPS compliance costs. Highlights: Benefits of satisfying U. S. renewable portfolio standards in 2013 were evaluated. Carbon dioxide (equivalent) was cut by 59 million metric tons (worth $2.2 billion). Reduced air pollution provided $5.2 billion in health and environmental benefits. Water withdrawals (830 billion gal) and consumption (27 billion gal) were reduced. Job/economic, electricity price, and natural gas price impacts were also evaluated.